The Impact on Non-Performing Loans in Indonesian Commercial Banks Caused by the Covid-19 Pandemic, Inflation, BI 7-Day Repo Rate, and Credit Interest Rates - Syahputri, Nisrina Anggi; Badriah, Lilis Siti; Arintoko; Hikmah, Maulia (Ijtimā iyya Journal of Muslim Society Research, 2025)
This study aims to examine the effect of the Covid-19 pandemic, inflation, the BI 7-Day Repo Rate (BI7DRR), and Credit Interest Rates on Non-Performing Loans (NPL) at Commercial Banks in Indonesia, both partially and simultaneously. This quantitative research, which explores rare phenomena such as the ongoing Covid-19 pandemic and empirical findings that partially reject the hypothesis and the loanable funds theory, offers novelty compared to previous studies. Using secondary data from March 2020 to March 2022 obtained from Bank Indonesia, the Financial Services Authority, and the Central Statistics Agency, this study applies multiple regression analysis with SPSS for Windows, employing t-tests, F-tests, and adjusted R² to measure the impact on NPL. The results show that partially, the Covid-19 pandemic and inflation do not affect NPL, while BI7DRR has a negative effect of 0.513% and Credit Interest Rates have a positive effect of 0.367% on NPL. Simultaneously, these four variables influence NPL by 52.2%, suggesting that Ho₅ is accepted and Ha₅ is rejected, which can be attributed to government and central bank fiscal policies as well as commercial bank credit relief programs for debtors. These findings imply the need for synergy among commercial banks, the central bank, and the government to navigate macroeconomic uncertainties through careful BI7DRR adjustments, competitive lending rates, credit restructuring, and stringent debtor evaluation, while encouraging debtors to enhance productivity and make well-informed credit decisions to prevent future NPL surges.